Effect of Taurine on The Respiratory System of Rats - E.M, Ammer; A.A., Shaaban; H.A., Ghonem; H.A., Elkashef (Journal of Food and Pharmaceutical Sciences, 2013)
The present study was designed to investigate the effect of taurine on isolated trachea and pulmonary artery of rats and the possible  mechanism(s) of action. The possible antioxidant effect  of  taurine  was  also  studied  by  measuring  its  protective  effect  against cyclophosphamide  induced  lung  injuiry.  Taurine  produced  a  concentration  dependent relaxation  in  the  isolated  tracheal  strips  and  pulmonary  arterial  rings  precontracted  by serotonin  (2x10-4 mM). The  relaxing effect of  taurine was not  influenced by pretreatment with  nitric  oxide  synthase  inhibitor  (L-NAME)  ,  cysteinyl  leukotreines  receptor  1  blocker (montelukast)  ,  H1  receptor  blocker  (chlorpheniramine)  ,  β-adrenoceptor  blocker (propranolol),  potassium  channel  blocker  (amiodarone)  ,  cyclo-oxygenase  inhibitor (indomethacin) or   muscarinic  receptor blocker  (atropine). Preincubation with  adenosine receptor blocker  (aminophylline) significantly potentiated  the  relaxing effect of  taurine  in the  tracheal  strips  and  pulmonary  arterial  rings.  Cyclophosphamide  (CYP,  150  mg/kg) administerated  i.p.  in  a  single  dose was  used  to  produce  lung  injuiry  in  rats.  CYP  caused marked  increase  in  lung  lipid peroxides  (MDA)  and  decrease  in  lung  reduced  glutathione (GSH).  Administration  of  taurine    (1%  in  drinking  water)  starting  7  days  before  CYP  and continuing  throughout  the  duration  of  the  experiment  (24  hours)  improved  significantly the lung GSH and MDA. It can be concluded that taurine relaxes precontracted rat tracheal strips and pulmonary arterial rings probably by direct effect on the smooth muscles. Also, the observed  antioxidant    activity of  taurine   which may  contribute  to  its  relaxant  effect suggesting the usefulness of turine in pulmonary hypertension.